Maďarská menšina v České republice: Zpráva z výzkumu - Holas, Jakub (Lidé města, 2010)
The Hungarian minority in the Czech Republic consists of several different groups of immigrants. Although this minority represents one unit, we have to distinguish between different groups of Hungarians. Primarily Hungarians from Slovakia and Hungary have both specific relations to the Czech majority, Czech language and Czech culture. Hungarians in the Czech Republic have established many national clubs and institutions, not only formally, but also informal associations established on the basis of friendships, gender or hobbies. These clubs serve to strengthen the national identity of Hungarians naturalized in the Czech Republic, to spread the Hungarian language and to serve as meeting points with other Hungarians living in the Czech Republic. At the same time, they provide opportunities to learn and practice the mother tongue for Hungarian children.